Securing Enterprises: Harnessing Blockchain Technology Against Cybercrime Threats - Fallen Zidan; Dimas Nugroho; Baskara Adi Putra (International Institute for Advanced Science & Technology (IIAST), 2023)
In the face of increasingly sophisticated cybercrime threats, large companies now need innovative solutions to protect their data and interests. Blockchain technology, which is based on the principles of decentralization and strong encryption, offers great potential in improving corporate cybersecurity. This research investigates the implementation of blockchain technology in the context of enterprise security by developing a blockchain-based dynamic system model. These findings make an important contribution in changing the way audits and general accounting operations are carried out, presenting fundamental changes in the profession. This new approach integrates blockchain technology into various aspects of cybersecurity, embracing innovation and creativity in the face of current challenges. By creating accurate computer models, this research brings a breakthrough in understanding system responses to employee fraud in corporate environments that adopt blockchain technology. This research aims to explore the potential of blockchain technology in improving corporate cybersecurity by identifying security gaps and designing effective updates, creating a safe and trustworthy digital environment for companies in this digital era. The findings of this research highlight the importance of integrating blockchain technology in auditing and general accounting operations, creating a foundation for the development of robust cybersecurity systems. In the context of companies using blockchain technology, this research reveals improved system responsiveness to employee fraud, indicating positive potential in mitigating security risks. This research provides a solid foundation for further development in the field of enterprise cybersecurity, inspiring innovation in protecting businesses and digital assets in a rapidly evolving cyberspace.